Customer Preference in Storing Wadiah Yad Dhamanah Savings (Survey at Bank BRI Syariah KCP Setiabudhi) - Jenio Yusma F (Universitas Pendidikan Indonesia, 2018)
This research aims to know the influence of product quality and service on the customer's preferences in-store savings wadiah yad dhamanah. The method used was an explanatory survey with a multiple linear regression test tool. The respondents of the research was Bank BRI Syariah KCP Setiabudhi Bandung. The sampling technique used is a sampling of saturated. The results showed that Bank BRI Syariah KCP Setiabudhi can be categorized and that significantly higher client preferences are influenced by the variable quality of product and service quality.